The Correlation between Maternal Vitamin D and Interleukin-17 Levels and Fetal Biophysical Profile - Mohammed, Rosol J.; Salih, Lina A. (Iraqi Journal of Science, 2021)
This research aims to evaluate the serum levels of vitamin D and interleukin 17 (Il-17) in pregnant women, then finding the correlation between these maternal parameters and fetus biophysical profile. Healthy pregnant women (n=45) and non-pregnant control (n=45) were involved in the study, who attended Baghdad medical laboratory, Baghdad, Iraq, with an age range of 20 to 40 years. An analytical study was conducted from October 2019 until January 2020.The results of the study show that the mean value of vitamin D level significantly increases (P≤0.05) in pregnant women (11.07±0.93 ng/ml) in comparison with that in non-pregnant control (8.03±0.69 ng/ml). The level of IL-17 was significantly higher (P≤0.001) in the pregnant women (468.38±50.62 Pg/ml) as compared to non-pregnant ones (144.39±3.98 Pg/ml). Also, the results show no significant correlation (0.162) between maternal vitamin D and (F.H.R.), which was measured by ultrasound sonography. Also, there is no significant inverse correlation between maternal Il-17 and fetal growth measurement.It can be concluded from the current study that some of the signs of the physical appearance of the fetus that were studied in the second trimester (13-28 w) and third trimester (29-41 w) of pregnancy do not correlate with the level of vitamin D in the mother’s blood. Also, there is a weak inverse relationship between this appearance and the mother’s immune response, represented by measuring the level of IL-17, which needs more studies in the future.